Reply to ’Is Liver Resection in Metastases of Exocrine Pancreatic Carcinoma Justified?’ - Singh, Amanjeet; Singh, Tanveer; Chaudhary, Adarsh (JOP. Journal of the Pancreas, 2011)
No abstract available. Image: Rai Bahadur Ganga Ram.